ANALISIS EKONOMI POLITIK KOMUNIKASI PADA HAK SIAR PERTANDINGAN SEPAKBOLA: Studi Deskriptif Praktik Spasialisasi Dalam Siaran Langsung Sepakbola Liga Eropa di Indonesia - ROY AMRI, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
The practice of spatialization in a process of looking at the political economy of communication opens up various possibilities about what can happen to the media industry. The growth of cable tv and the increasing number of subscribers prove that distance, time, cost, and other regulatory conditions are no longer a problem. Football fans in Indonesia now have to subscribe to cable tv and / or internet tv applications to be able to watch their favorite clubs compete. Football broadcasts, especially those featuring matches from the best European clubs, are a commodity that has the potential to sell well in the sports fans' market. However, the policies of organizers in the countries of origin of these leagues require ownership of broadcast rights to be able to broadcast live. This prerequisite was also welcomed by several cable tv operators and internet tv channels by purchasing the broadcast rights to win Indonesian viewers. The monopoly of investment returns that reached trillions of rupiah in its development in Indonesia did not make cable TV consumer candidates poor choices. Other cable TV operators that do not have broadcast rights have not lost their prestige in the eyes of football fans. The operators then “worked together” to offer the same program.And football fans are automatically bound to become subscribers to certain cable TV operators or certain digital platforms.